Exercise technique: counterbalance skater squat - Cook, J.; Ryan, G. A. (Strength and Conditioning Journal, 2022)
This column provides a detailed description of the correct technique for the counterbalance skater squat. This exercise is a unique variation of the single leg squat: the counterbalance skater squat. The use of this exercise can aid in the development of unilateral strength and hypertrophy benefiting those who are required to sprint and change direction regularly. Additionally, this column outlines set and repetition recommendations and progressions through the lift.